Pedagogia da alternância e formação do jovem na Casa Familiar Rural de Coronel Vivida – PR: avanços, limites e desafios - Detogni, Andreia Aparecida (2017)
The main objective of this research was to analyze the alternating youngster’s formation at the Rural Family House of Coronel Vivida – PR in order to understand the possible limits and challenges of the insertion of the young alternating in the rural property and the way the family receives and assists in this practice. Thus, semi-structured interviews were conducted with the young alternates, enrolled in the last year of the "Technical Course on Food" of the Rural Family House, and their families. The research subjects are eight (08) young and seven (07) families. The study was carried out through a qualitative approach based on the Dialectical Materialism method, the research elements consisted of bibliographical and documentary research, having as reference sources, papers which refer to the topics discussed, such as Gramsci (2000), Caldart (2003) ), Saviani (2007; 2012), Molina (2006; 2015), Passador (2006), Guedin (2012), Estevam (2012) and Ribeiro (2013). The aim was to understand the field, its contradictions, modernization and implications in the history of its people, as well as the comprehension about the purposes and contributions of PA in the lives of young people and their families. In this way, it became possible to constitute elements for an analysis regarding the proposal of PA developed at the Rural Family House of Coronel Vivida – PR, which made it possible to observe and verify the potentialities and limitations of this training proposal. As result, we highlight the advances in Alternacy Pedagogy such as the reduced number of students in class, the full study period, the safety of the alternating youngsters, and the personalized attendance developed by the instructors and teachers. As limit conditions, we observe the lack or absence of practice in family ownership of the knowledge learned and discussed in the Family House, its weak physical structure, and its adequacy to different theoretical aspects which don’t take the work/ job as an educational principle, leading to a practice that strives to adapt to the current social situation.